Community Accounting School: Basic accounting training for administrators of cooperatives, foundations and community organizations - Muslim, Muslim; Sonjaya, Yaya; Prasetianingrum, Septyana (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to evaluate the effectiveness of basic accounting training developed through the Community Accounting School approach for administrators of cooperatives, foundations, and community organizations at the grassroots level. The primary focus is to understand how this training contributes to improving accounting literacy, financial transparency, and institutional accountability. Research Design and Methodology: This study uses a Systematic Literature Review (SLR) approach by critically examining findings from various relevant scientific articles, both national and international. The analytical framework is based on the Community of Practice (CoP) approach, which emphasizes the importance of collaborative and contextual learning within communities of practitioners. Findings and Discussion: The main findings indicate that accounting literacy in community organizations remains low, which has a negative impact on their financial management. Practical accounting training, such as cash recording and simple report preparation, has been proven to increase awareness of transparency and shape a culture of collective accountability. The social and participatory learning process strengthens the community's identity as an entity capable of managing its finances independently. Implications: This study provides practical contributions to local governments, educational institutions, and community empowerment agencies in developing more adaptive training programs based on local needs. The Community Accounting School model offered can be widely replicated to strengthen community institutional capacity sustainably.